PENGARUH PEMBERIAN STIK DAUN KELOR TERHADAP PENINGKATAN NAFSU MAKAN DAN BERAT BADAN BALITA - Wahyuni Wahyuni; Vedjia Medhyna; Fera Hermalina (Universitas Fort de Kock Bukittinggi, 2023)
Decreased immune system and nutritional problems in children under five have a bad impact on the health of children under five for their growth and development. One way that can be done is by utilizing natural ingredients such as Moringa leaves which are processed into foods that are liked by toddlers. The purpose of this study was to determine the effect of giving Moringa leaf sticks to the increase in appetite and weight of toddlers aged 2-5 years in the working area of the Lubuk Gadang Health Center in 2022. The study was conducted in September 2021-March 2022. The research design used was a quantitative study. with a quasi-experimental design of One Group Pretest and Posttest. The population in this study were children aged 2-5 years from October - December 2021 as many as 32 people. The sampling technique is Total Sampling. The data used are primary data and secondary data. Data analysis was carried out univariate and bivariate using the Paired Sample T-Test. The results showed that from the Normality test, the significance value was > 0.05, the data was normally distributed, the univariate test found that the distribution of toddlers' appetite before was more than half of the respondents, 14 people (43.8) had a good appetite, toddler's appetite after that was more from half of the respondents 19 people (59.4) had sufficient appetite, the average weight of toddlers was 12.85 kg to 13.53 kg before and after being given Moringa leaf sticks, and there was a significant effect between appetite and body weight. toddlers before and after being given Moringa leaf sticks with a P-Value value of 0.000 <0.05. Based on the results of the study, it was concluded that there was a significant effect between appetite and toddler body weight before and after being given Moringa leaf sticks. So it is recommended for the working area of the Lubuk Gadang Health Center to often provide innovative complementary foods to toddlers in order to improve the nutritional status of toddlers in Lubuk Gadang